Taking Behavioral Genetics Seriously - Parens, Erik (The Hastings Center report, 1996)
Discussions of information produced by genetics research are often guided by two mistaken theoretical moves. Enthusiasts tell us not to worry because genetic tinkering can alter only our body, never our soul; worriers suggest that discovering links between our behavior and our different bodies threatens important democratic ideas like moral equality. If we understand the body and soul to be inseparable and equality to be undiminished by difference, we can begin to take seriously the information produced by genetics research.